DO INVESTORS REACT TO PERPETUAL BOND ANNOUNCEMENTS IN ASEAN? EVIDENCE FROM AN EVENT STUDY - Erwin Manurung; Ronald Rulindo (Eduvest - Journal of Universal Studies, 2025)
This study examines how investors in ASEAN respond to announcements of perpetual bond issuance and whether firm-level characteristics influence the strength of market reactions. Based on 99 announcement events from 2019 and 2021-2024, the analysis employs an event study methodology combined with cross-sectional multiple linear regression. Cumulative abnormal return (CAR) over the (-1, +1) event window is used to capture short-term market responses, and is adjusted through one-sided winsorization to mitigate the influence of extreme positive values. The results show a significantly positive average CAR, suggesting that investors generally react favorably to such announcements. In the main regression model, the debt to equity ratio (DER) has a significant negative effect on CAR, while market return prior to the announcement (MR) has a significant positive effect. Other variables, including book to market ratio (BM), return on assets (ROA), and bond rating, are not statistically significant. Additional analysis with sector dummies reveals stronger responses for financial firms and a significant effect for BM, while country dummies show no notable variation across ASEAN markets. These findings suggest that capital structure and sectoral context play important roles in shaping investor perceptions of hybrid financing instruments such as perpetual bonds.